2018
DOI: 10.1371/journal.pone.0194749
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidities on the prognoses of trauma patients: Analysis of a hospital-based trauma registry database

Abstract: Here we conducted a retrospective analysis of hospital-based trauma registry database for evaluating the impacts of comorbidities on the prognosis for traumatized patients using Index of Coexistent Comorbidity Disease (ICED) scores. We analyzed the data of patients with blunt trauma who visited emergency department between January 1, 2011, and December 31, 2015 in Chang-Gung Memorial Hospital, Keelung branch, a single level I trauma center in the Northern Taiwan. All consecutive patients with blunt trauma who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 45 publications
0
14
1
2
Order By: Relevance
“…The study concluded that comorbidities have an important influence on long-term outcomes after major trauma. In addition, Wang et al 11 analyzed their hospital trauma registry database at the Chang Gung Memorial Hospital, Keelung, a single Level I trauma center in North Taiwan, between 2011 and 2015. Patients with penetrating injuries, burns, out-of-hospital cardiac arrest, incomplete medical history, age younger than 20 years, and discharge or death within 24 hours of admission were excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that comorbidities have an important influence on long-term outcomes after major trauma. In addition, Wang et al 11 analyzed their hospital trauma registry database at the Chang Gung Memorial Hospital, Keelung, a single Level I trauma center in North Taiwan, between 2011 and 2015. Patients with penetrating injuries, burns, out-of-hospital cardiac arrest, incomplete medical history, age younger than 20 years, and discharge or death within 24 hours of admission were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher comorbid scores accounted for mortality among traumatized patients with ISS < 25, particularly among patients with ISS < 16. 11 Interestingly, a study carried out by Shoko and his associates asked the question whether preexisting medical conditions (PMCs) may play a role in hospital mortality. 12 The study involved a retrospective analysis using 20,257 cases recorded in the Japan Trauma Data Bank from 2004 to 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, naive CSE knock out (ko) mice had lower levels of OTR [1], and similarly, naive mice with a genetic deletion of OTR presented with a reduction of CSE expression [14]. Psychological stress can reportedly dysregulate OTR expression [16], and trauma leads to cardiovascular co-morbidities, which increase morbidity and mortality in intensive care patients [1,17,18]. Trauma can be a result of either (or both) a deep emotional pain, and/or a life-threatening event (psychological) or a physiological injury or impact against the body (physical).…”
Section: Introductionmentioning
confidence: 99%
“…The gasotransmitter hydrogen sulfide (H 2 S) (endogenously produced by cystathionine γ-lyase (CSE), cystathionine β-synthase (CBS) and 3-mercaptopyruvate-sulfurtransferase (3MST) (as depicted in Figure 1 )) and the neuroendocrine oxytocin (OT) system have been recently shown to not only possibly play parallel roles in the heart and the brain in response to trauma, but also to influence one another. Trauma can lead to cardiovascular impairments and disease which worsens the outcomes of intensive care patients and increases morbidity and mortality [ 1 , 2 ]. Trauma is either a consequence of a deep emotional pain or a physical injury.…”
Section: Introductionmentioning
confidence: 99%